2017
DOI: 10.1017/s002185961700051x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and white clover impacts on the management of perennial ryegrass–clover swards for grazing cattle

Abstract: SUMMARYPerennial ryegrass and white clover (WC) have been shown to form compatible mixtures for pasture production under temperate climates. The inclusion of WC has the potential to enhance the performance of grass swards, but the extent of the improvement under contrasting grazing management strategies is unclear. Grazing rotation and fertilizer nitrogen (N) use have been identified as two major factors that can influence the performance of grass–clover swards. The objective of the current study was to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 43 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…In artificial cultivation, the mixed planting method of leguminous and gramineous plants is usually adopted to build grassland. Compared with monoculture grassland, the mixed planting of grassland not only has advantages in improving forage yield and quality [5][6][7] but also plays an obvious role in improving soil fertility and realizing systematic sustainable production [8]. In a grazing experiment in Canada, Chen et al [9] found that total amounts of N 2 fixed in Medicago sativa and Poa pratensis mixed pastures were sufficient to replace N fertilizer and sustain plant protein for grazing compared with grass-only pastures.…”
Section: Introductionmentioning
confidence: 99%
“…In artificial cultivation, the mixed planting method of leguminous and gramineous plants is usually adopted to build grassland. Compared with monoculture grassland, the mixed planting of grassland not only has advantages in improving forage yield and quality [5][6][7] but also plays an obvious role in improving soil fertility and realizing systematic sustainable production [8]. In a grazing experiment in Canada, Chen et al [9] found that total amounts of N 2 fixed in Medicago sativa and Poa pratensis mixed pastures were sufficient to replace N fertilizer and sustain plant protein for grazing compared with grass-only pastures.…”
Section: Introductionmentioning
confidence: 99%